The Role of FM Radio Stations in Promoting Local Sports in Kenema City, Eastern Sierra Leone (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
ABSTRACT: Background: Local sports in Kenema City, Eastern Sierra Leone, often suffer from low visibility and limited institutional support. FM radio is the most accessible medium in the region, yet its specific role and effectiveness in promoting local sports remain under-examined.Objectives: This study assessed the strategies used by FM radio stations in Kenema to promote local sports, examined listener perceptions and attitudes, and identified the challenges faced by sports presenters.Methods: A mixed-methods approach was employed. Quantitative data were collected via structured questionnaires from 120 listeners and stakeholders. Qualitative data were gathered through 10 interviews with sports presenters and 3 focus group discussions with community sports fans. Data were analyzed using descriptive statistics and thematic content analysis.Findings: Findings indicate that while most FM stations offer sports coverage, programming is often irregular and lacks depth. Key promotional strategies include discussions (33.3%), call-in shows (16.7%), and interviews (16.7%). Coverage is heavily dominated by international football (79.2%), with local sports receiving minimal attention. Listeners value sports programming for community cohesion but report dissatisfaction due to presentation quality and perceived bias. Presenters face significant constraints, including inadequate funding (33.3%), lack of training (33.3%), and poor equipment.Conclusion: FM radio holds significant potential to enhance local sports promotion in Kenema. However, structural and capacity limitations hinder its effectiveness. Stations should establish regular, dedicated sports slots, improve presenter training, and actively engage with local sports associations. Diversifying coverage beyond football is critical for fostering a more inclusive local sports culture.